Role of Synchronized Lifestyle Modification Program and Physiotherapy in Peripheral Neuropathy in Insulin Dependent Type 2 Diabetics - Tayyaba Anis Chaudhry, Shazia Ali, Shagufta Feroz, Rubab Rameez, Ayesha Zafar, Fatima Iqbal, Humaira Fayyaz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Distal symmetrical polyneuropathy is the most common form of diabetic peripheral neuropathy. Management of peripheral neuropathy through dietary modification and exercise synchronized with circadian rhythm optimizes metabolic parameters, thus restoring nerve functions. Aim: To determine the effect of Synchronized lifestyle modification program (SLP) and Physiotherapy on Michigan neuropathy screening instrument (MNSI), Fasting blood glucose (FBG), HbA1c, Lipid profile and Nerve conduction studies (NCS) in insulin dependent type 2 diabetic neuropathy patients. Study Design: Randomized Controlled Trial Place and Duration: Study was carried out in Physiology department of Islamic International Medical College (Riphah international University) in collaboration with Physiotherapy Department, Railway Hospital, Rawalpindi for a duration of 1 year from October 2020 to October 2021. Methodology: 120 Type 2 diabetic neuropathic patients on insulin were recruited after written informed consent. Baseline evaluation included; assessment of lifestyle pattern, MNSI, FBG, HbA1c, lipid profile and NCS. Patients were divided into Group A (Control) and Group B (Experimental). Group B was subdivided into Group B1 who received SLP, Group B2 received combined SLP and Physiotherapy and Group B3 received Physiotherapy for 12 weeks. Analysis of parameters was done by repeated measure ANOVA. p≤0.05 was considered as significant. Results: MNSI, FBG, HbA1c, serum cholesterol, TGs and LDLs were significantly improved in Group B2. HDL levels and Nerve conduction parameters were not found to be significant. Conclusion: Combined Synchronized Lifestyle Modification Program and Physiotherapy is more effective in type 2 diabetic neuropathy patients on Insulin. Keywords: Synchronized lifestyle modification programme, Diabetic peripheral neuropathy, Distal symmetrical polyneuropathy.